2017
DOI: 10.5455/ijmsph.2017.1059706122016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection and response to hepatitis B vaccination among Egyptian school children

Abstract: Background: A prevalence of hepatitis C virus (HCV) infection is relatively low in children as it was 3% and 9% in the upper and lower Egypt areas, respectively. Most chronic hepatitis C patients are asymptomatic and unaware of their disease before diagnosis. Similarly, hepatitis B virus (HBV) is a major cause of chronic liver disease, particularly cirrhosis and hepatocellular carcinoma, though HBV incidence and infection has been markedly reduced after mass vaccination programs. Objectives: To identify the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This meta-analysis result was also in line with a study conducted in Egypt, Alexandria, with 58.5% of the participants were an anti-HBs level > 10 mIU/ml [ 22 ], and 47.62% of the vaccinated children responded to the HBV vaccine with an anti-HBs level > 10 mIU/ml [ 21 ]. The protective level of children younger than 6 was 95.2%, but 41.7% was in children older than six [ 21 ].…”
Section: Discussionsupporting
confidence: 85%
“…This meta-analysis result was also in line with a study conducted in Egypt, Alexandria, with 58.5% of the participants were an anti-HBs level > 10 mIU/ml [ 22 ], and 47.62% of the vaccinated children responded to the HBV vaccine with an anti-HBs level > 10 mIU/ml [ 21 ]. The protective level of children younger than 6 was 95.2%, but 41.7% was in children older than six [ 21 ].…”
Section: Discussionsupporting
confidence: 85%
“…Three (75%) out of the four positive cases for the anti-HCV were females while one was a male. (15) In this study (Table 3), blood transfusion is a significant risk factor for HCV infection (p=0.029) and it is like Barakat SH et al, 2011, Egypt, they found that the most significant risk factors for anti-HCV positivity include blood transfusion, dental procedures, surgery and intravenous catheterization (12) . These findings also agree with Abed N T, et al (2016).…”
Section: Discussionmentioning
confidence: 64%
“…According to the Egypt Health Issues Survey 2015 (EHIS) percentage of positive HCV antibody test (10-14 years) was 0.7%, and percentage of positive HCV antibody test (15-19 years) was 1% . (12) On the other hand, Abed N T, et al (2016), Benha, Egypt screened Six hundred children (6-17 years) for HCV antibodies (HCV Ab) and hepatitis B surface antibody concentration (HBsAb). Regarding HCV, 4.7% of children were diagnosed as HCV seropositive by ELISA for anti-HCV.…”
Section: Discussionmentioning
confidence: 99%